Occurrence and severity of myasthenic crisis in an unselected Turkish cohort of patients with myasthenia gravis - Ozyurt Kose, Selen; Nazli, Ezgi; Tutkavul, Kemal; Gilhus, Nils Erik (Frontiers in Neurology, 2023)
Myasthenia gravis (MG) is a disorder at the neuromuscular junction that can deteriorate into a MG crisis with weakness of bulbar and respiratory muscles. In this study, we describe the clinical manifestations during MG crisis, identify risk factors, and examine treatment and outcome. This retrospective study included all 95 patients who had generalized MG in our center during the last 10 years period. We collected the patients' data including clinical follow-ups, muscle antibodies, thymic status, and treatments. Characteristics of patients with and without crisis were compared. Features of all MG crises were assessed.Twelve (13%) of the patients developed a MG crisis, during the observation period. Men were more often affected at older age. Seven patients experienced multiple MG crises. Thymoma increased the risk for a MG crisis, whereas thymic hyperplasia decreased the risk. MG crises were more common in the summer months. No patients died during a MG crisis. Risk factors for a MG crisis were thymoma, older age, MuSK antibodies, and previous MG crises.Individualized and active immunosuppressive treatment and optimal intensive care during crises provide a good outcome for patients with generalized MG.